2015
DOI: 10.1152/ajpregu.00440.2014
|View full text |Cite
|
Sign up to set email alerts
|

Renin knockout rat: control of adrenal aldosterone and corticosterone synthesis in vitro and adrenal gene expression

Abstract: The classic renin-angiotensin system is partly responsible for controlling aldosterone secretion from the adrenal cortex via the peptide angiotensin II (ANG II). In addition, there is a local adrenocortical reninangiotensin system that may be involved in the control of aldosterone synthesis in the zona glomerulosa (ZG). To characterize the long-term control of adrenal steroidogenesis, we utilized adrenal glands from renin knockout (KO) rats and compared steroidogenesis in vitro and steroidogenic enzyme express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…18 This mechanism may be important in the Ren −/− rats since it was previously shown that serum potassium was significantly increased in Ren −/− rats. 41 The authors also demonstrated in vitro that the corticosterone basal levels and production by zona reticularis/fasciculata cells in response to cyclic adenosine monophosphate (cAMP) was unaffected in the Ren −/− rat compared with the Ren +/+ controls. Our in vivo experiments accordingly revealed equal plasma levels of corticosterone in Ren −/− and Ren +/+ littermates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 This mechanism may be important in the Ren −/− rats since it was previously shown that serum potassium was significantly increased in Ren −/− rats. 41 The authors also demonstrated in vitro that the corticosterone basal levels and production by zona reticularis/fasciculata cells in response to cyclic adenosine monophosphate (cAMP) was unaffected in the Ren −/− rat compared with the Ren +/+ controls. Our in vivo experiments accordingly revealed equal plasma levels of corticosterone in Ren −/− and Ren +/+ littermates.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, recent studies using this model defined basal and cAMP-stimulated aldosterone production in the zona glomerulosa cells. 41 Further characterization of sodium balance in these animals is required as we hypothesize that low systemic RAAS activity is the cause of very low blood pressure (~60 mmHg) in these animals. 11 …”
Section: Discussionmentioning
confidence: 99%
“…It was observed that Ren −/− rats experienced a reduction of about 50 mmHg in their blood pressure in comparison to Ren +/- littermates, when on low-salt diet (0.4% NaCl) ( Moreno et al, 2011b ). In their pivotal work, Moreno and colleges suggested that the decrease in basal blood pressure of renin knockout rats was due to an attenuation in the steroidogenesis process occurring in the zona glomerulosa of the adrenal cortex ( Raff et al, 2015 ). Furthermore, the expression and activity of renal sodium channels and transporters were significantly dysregulated in renin-deficient salt-sensitive rats ( Pavlov et al, 2016 ).…”
Section: Genetic Background Of Salt-sensitive Hypertensionmentioning
confidence: 99%